Commemorative dates re-signified in the early years: didactic activities in Science and Mathematics guided by the National Curricular Common Base (Research, Society and Development, 2022)
This study aims to investigate how commemorative dates can be worked on in the Teaching of Science and Mathematics in the Early Years, aiming at their resignification in the school context and the articulation with the National Curricular Common Base. Education undergoes constant changes to keep up with society's demand. It is very important that the teacher is aware that the search for training is a process for his entire professional life. The purpose of this work consisted of planning and creating a Pedagogical Notebook, with suggestions for activities for each date under study: Peace Day, Women's Day, World Water Day, Indian Day, September 7 and Gaucho Day. In each activity there is a description of the target audience, the object of knowledge and the skills that will be developed in the students with each proposed activity, in addition to the description of the activities that are presented for moments. The Pedagogical Notebook aims to suggest methodological strategies for the development of some pedagogical activities, articulating the commemorative dates with the Teaching of Science and Mathematics, in the Initial Years of Elementary School. The application of this work took place through a conversation circle between the students of the Integrated Seminar II discipline, of the Postgraduate Program in Science and Mathematics Teaching, of the Professional Master's Degree, at the Franciscan University. It is worth mentioning that all the students who participated in the activity, a total of 11 people, are Basic Education teachers.